2007
DOI: 10.1007/s10704-007-9093-2
|View full text |Cite
|
Sign up to set email alerts
|

Crack growth in cylindrical aluminum shells with inner reinforcing foam layer

Abstract: The occurrence of cracks in aging aircraft fuselage is major problem in the airline industry. The remaining life of the aircraft is strongly dependent on the residual strength of its structure. Residual strength is affected by crack sizes and their growth rates. In the case of a longitudinal crack in a pressurized cylinder (as in the case of an aircraft fuselage), the geometry and loading conditions cause the edges of the crack to bulge out generating a complex stress field around the crack tips; this is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Experimental studies were conducted by Bakuckas et al [4] and Lazghab et al [5] showed that this solution could increase fatigue life by 161%. A numerical study conducted by Lazghab et al [6] showed that the bulging factor could be reduced by as much as 45%. The bulging factor is a parameter defined as the ratio of the stress intensity factor (SIF) of a through crack in curved shell to the stress intensity factor of the same crack in a flat plate of the same thickness as the shell as given in Eq.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies were conducted by Bakuckas et al [4] and Lazghab et al [5] showed that this solution could increase fatigue life by 161%. A numerical study conducted by Lazghab et al [6] showed that the bulging factor could be reduced by as much as 45%. The bulging factor is a parameter defined as the ratio of the stress intensity factor (SIF) of a through crack in curved shell to the stress intensity factor of the same crack in a flat plate of the same thickness as the shell as given in Eq.…”
Section: Introductionmentioning
confidence: 99%
“…It has been treated extensively in the literature, a few representative works are [6][7][8][9][10][11][12][13]. Generally the stress conditions near the crack tip in a curved shell are more severe than its counterpart in a flat plate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actuellement, la plupart des approches numériques utilisées pour caractériser les tolérances à l'endommagement sont basées sur la méthode des éléments finis classique FEM [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. La méthode des éléments finis étendus XFEM couplée à la méthode des surfaces de niveau LSM permet de concevoir des maillages indépendants de la géométrie de la fissure sans recours aux stratégies de maillage et de remaillage [16] et [17] donc une réduction considérable du délai de maillage, étape souvent couteuse et sans valeur ajoutée.…”
Section: Introductionunclassified